(untitled) (GEOMATE Journal, 2025)
The paper investigates the load-bearing capacity of bored piles in uneven sandy soil conditions, an important issue in the design of deep foundations for large construction projects. The research aims to analyze the relationship between load and vertical displacement of the bored piles while determining the maximum bearing capacity of the pile in a sandy environment with uneven characteristics. The methodology includes numerical simulation using PLAXIS 3D software combined with field tests to analyze the displacement changes of the piles under different load levels. The results indicate that the displacement does not follow a linear relationship but increases rapidly once the load exceeds 17000 kN, with significant settlement observed as the load increases. The cubic regression model applied in this study shows high accuracy, with an R² value of 0.997, meaning that 99.7% of the displacement variation can be explained by the load change. The maximum bearing capacity of the bored pile is determined to be 13495.73 kN, indicating the load limit that the pile can withstand before significant settlement occurs. The research contributes to improving deep foundation design in uneven sandy soil conditions and provides useful tools for engineers and designers to assess the load-bearing capacity of bored piles, thereby optimizing foundation construction solutions for real-world construction projects.